MARKET ORIENTATION AND INNOVATION PERFORMANCE: THE MEDIATING ROLE OF ENTREPRENEURIAL STRATEGIC POSTURE - Zehir, Cemal; Karaboga, Tugba; Karaboga, Hasan Aykut; Uzmez, Ahmet (FUTURE ACAD, 2019)
Many studies have investigated the effect of marketing orientation (MO) on firm performance generally from a financial performance perspective. But the effect of MO on innovation performance is not studied deeply. Also, it is understood from the literature that MO and entrepreneurial strategic posture (ESP) of a company are closely related terms and these two concepts are studied together in different studies. We treated ESP as a firm's strategic tendency to take entrepreneurial activities. This concept is similar to entrepreneurial orientation, corporate entrepreneurship, entrepreneurial proclivity and entrepreneurial strategy making concepts in the literature. In this study, the mediating effect of ESP on MO dimensions (customer orientation, competitor orientation and inter functional coordination) and innovation performance relationships are studied. The survey of this study applied to 698 managerial positions of 238 manufacturing companies. Data analyses were conducted with SPPS program with firm level data. Analyses results indicated that MO has a significant direct effect on ESP and innovation performance. Also, ESP has a mediating effect on the sub dimensions of MO and innovation performance relationships. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Market orientation; entrepreneurial strategic posture; innovation performance; LEARNING ORIENTATION; CORPORATE ENTREPRENEURSHIP; CUSTOMER ORIENTATION; MANAGEMENT; FIRMS; KNOWLEDGE; INTEGRATION; PROCLIVITY; TRANSITION; ADVANTAGE; Business & Economics